Double swing chair - Moftar, Mohammad Faize; Che Lah, Che Mohamad Azrul; Omar, Alias; Mat Yuti, Muhamad Arbain (2012)
This study is to discuss about new design of swing chair made from wood and the durability of the wood. This design takes several types of heavy hardwood such as Merbau and Resak. The use of wood is also to increase the aesthetic value of the product. Other than that, this study also to find more information about the design of swing chair.